ANTIOXIDATIVE AND FUNCTIONAL PROPERTIES OF PLUM OIL CAKE PROTEIN ISOLATE PREPARED BY DIFFERENT DRYING METHODS - Pantić, Jovana (Food and Feed Research, 2024)
The global demand for proteins is constantly increasing, so that science and industry have to explore novel raw materials for protein extraction. Plum oil cake, which is obtained after plum oil cold pressing, has great potential in terms of low-cost material and nutritional composition. The high protein content (up to 50%) of this by-product is ideal for valuable protein-rich ingredients extraction. Protein isolates from plum oil cake (PPI) were prepared using different drying methods- thermal drying (PPIT) and freeze-drying (PPIF). Obtained isolates were compared in terms of their antioxidative properties and functionality. Protein content and process yield were also examined, resulted in high protein content (over 96%), with no influence of drying method. Light color of PPIF would be more appealing for consumers and more suitable for incorporation in food systems. Functional properties were not significantly affected my different drying methods, except for protein solubility. Both PIs exhibited minimum protein solubility at pH 5.0 and maximum solubility at pH 10.0, while PPIF was much more soluble compared to PPIT. The freeze-drying method led to a much higher antioxidant activity of PPIF. Overall, protein isolates from plum cake obtained from different processing methods differed in appearance, solubility and antioxidant capacity, but yield, protein content and other functional properties were similar. This information will be useful to optimise the production of this protein isolate and benefit its applications.